Assessing Job Application Skills in English for Business: A Study of Fourth-Semester Students at Politeknik Negeri Jember - Setia Budi, Agus; Zuhro, Cholimatus (Journal of English in Academic and Professional Communication, 2024)
In the era of globalization, proficiency in English for business purposes is essential for career success and expanding professional opportunities. This study examined the job application skills of fourth-semester students enrolled in the English Study Program at Politeknik Negeri Jember during the 2023/2024 academic year, specifically those participating in an English for Business class. Utilizing a quantitative descriptive research approach, data were collected through a pre-test designed to assess students' knowledge in finding job vacancies, writing cover letters, preparing resumes, and attending job interviews. The pre-test consisted of 41 items categorized into these four areas. The results revealed strong performance among students, with the majority scoring in the high range (80-100), indicating strong proficiency in job application skills. The difficulty index for each section of the pre-test showed that students found the questions generally easy, with job interviews perceived as the easiest and resumes as relatively more challenging. These findings emphasize the importance of English for Business classes in equipping students with essential skills for entering the competitive global job market. The study suggests that practices in job applications and English proficiency improvement can enhance students' readiness for professional careers in an international context.